Deterministic processes drive turnover-dominated beta diversity of breeding birds along the central Himalayan elevation gradient - Zhifeng Ding; Jianchao Liang; Le Yang; Cong Wei; Huijian Hu; Xingfeng Si (Avian Research)
Beta diversity, the variation of community composition among sites, bridges alpha and gamma diversity and can reveal the mechanisms of community assembly through applying distance-decay models and/or partitioning beta diversity into turnover and nestedness components from functional and phylogenetic perspectives. Mountains as the most natural experiment system provide good opportunities for exploring beta diversity patterns and the underlying ecological processes. Here, we simultaneously consider distance-decay models and multiple dimensions of beta diversity to examine spatial variations of bird communities, and to evaluate the relative importance of niche-based and neutral community assembly mechanisms along a 3600-m elevational gradient in the central Himalayas, China. Our results showed that species turnover dominates taxonomic, functional, and phylogenetic beta diversity. We observed strongest evidence of spatial distance decays in taxonomic similarities of birds, followed by its phylogenetic and functional analogues. Turnover component was highest in taxonomic beta diversity, while nestedness component was highest in functional beta diversity. Further, all correlations of assemblage similarity with climatic distance were higher than that with spatial distances. Standardized values of overall taxonomic, functional, and phylogenetic beta diversity and their turnover components increase with increasing elevational distance, while the standardized values of taxonomic and phylogenetic nestedness decreased with increasing elevational distance. Our results highlighted the niche-based deterministic processes in shaping elevational bird diversity patterns that were determined by the relative roles of decreasing trend of environmental filtering and increasing trend of limiting similarity along elevation distances.